The societal factors of the psychological well-being of non-religious people - I. Yahiiaiev (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
As it has been shown by the recent studies, religious people, on average, report higher rates in different measures of happiness and well-being, their social self-esteem and psychological adjustment are healthier, even their tweets are more positive than atheists’ ones. However, findings re- main controversial, and there is an evidence of the more complex nature of these facts. The psychological benefits of religiosity are not intrinsic and universal but socially and culturally specific. In affluent and democratic countries religious and non-religious individuals experience the same level of well-being. The relationship between religiosity and psychological well-being is dependent on the broader context. The question should not be whether religiosity boosts happiness, but in what conditions and for whom. In particular, there are factors, which mediate the religious contribu- tion to psychological well-being. They may be conventionally divided into societal and individual. The societal factors are religious or secular char- acter of society, general attitude towards religion, the congruence of personal and societal values, social engagement and support, provided by the religious or secular community. Religious people enjoy psychological benefits in cultures that tend to value religiosity. Non-religious people are happier in the secular societies because they may express their views free and get more like-minded friends. People are happier when they fit in with the dominant characteristics of the culture of their society. The psychological benefits of religiosity are, apart from other factors, shaped by social context, dominant values in the given society and societal conformity mechanisms.